2022
DOI: 10.5897/ajfs2022.2172
|View full text |Cite
|
Sign up to set email alerts
|

Food safety practices of cooked food hawkers in Tharaka Nithi County, Kenya

Abstract: Hawking of cooked foods is an important economic activity, especially for low-income earners. However, the trade raises public health concerns particularly due to the likely breaches of food safety standards. Thus, this study investigated the food safety practices of hawkers of cooked foods in Tharaka Nithi County. A cross-sectional study design was used to collect data from 151 respondents using a questionnaire. The other data collection tools included a key informant interview guide and an observation checkl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Many of the vendors were handling food with bare hands, did not cover their food, and did not wear hairnets and aprons, similar findings have been reported elsewhere. 6,18,25 Like in previous studies, many of the vendors did not wash their hands after handling money and yet currency notes and coins have been found to be contaminated with pathogenic bacteria as well as fungi and yeast. 18,26,27 Having uncovered hair is likely to contaminate the SF as hair has been found to harbor Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Many of the vendors were handling food with bare hands, did not cover their food, and did not wear hairnets and aprons, similar findings have been reported elsewhere. 6,18,25 Like in previous studies, many of the vendors did not wash their hands after handling money and yet currency notes and coins have been found to be contaminated with pathogenic bacteria as well as fungi and yeast. 18,26,27 Having uncovered hair is likely to contaminate the SF as hair has been found to harbor Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 72%
“…6,18,25 Like in previous studies, many of the vendors did not wash their hands after handling money and yet currency notes and coins have been found to be contaminated with pathogenic bacteria as well as fungi and yeast. 18,26,27 Having uncovered hair is likely to contaminate the SF as hair has been found to harbor Staphylococcus aureus. 28 Coupled with the fact that the SFVs in this study did not practice social distancing, lacked personal protective equipment (PPE), and did not wash their hands, while others were blowing air into the food bags and only 24% were cleaning their work surfaces frequently, showed that they did not follow COVID-19 guidelines that were in place during the study period which exposed their customers to respiratory diseases such as colds and COVID-19.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations